Out of Flamingoes - An Exodus - Burnett, Trevor (Express)
Trevor Burnett recounts the origins and development of the steelband Exodus. In 1981, a group of players from the Flamingoes Steel Orchestra left that band and became the nucleus of a group aptly called Exodus.
Keywords: Steel bands (Music) -- Trinidad and Tobago -- History; Exodus (Musical group); Steel band music -- Trinidad and Tobago